Absolute configuration assignment of a chiral molecule in the gas phase using foil-induced Coulomb explosion imaging - Herwig, Philipp; Zawatzky, Kerstin; Schwalm, Dirk; Grieser, Manfred; Heber, Oded; Jordon-Thaden, Brandon; Krantz, Claude; Novotný, Oldřich; Repnow, Roland; Schurig, Volker; Vager, Zeev; Wolf, Andreas; et al. (Physical review. A, Atomic, molecular, and optical physics, 2014)
Chiral molecules exist in two configurations that are nonsuperposable mirror images of one another. The underlying molecular structure is referred to as the absolute configuration. In chiral environments, the handedness of molecules influences their chemical characteristics dramatically, and therefore the determination of absolute configurations is of fundamental interest in organic chemistry and biology. Commonly applied techniques to assign absolute configuration are anomalous single-crystal x-ray diffraction and vibrational circular dichroism. However, these techniques become increasingly more challenging when applied to molecules that are made out of light atoms exclusively. Furthermore, there is no established method to determine the absolute handedness of gas-phase molecules that are not optically active. In this work, we apply the foil-induced Coulomb explosion imaging technique to determine directly the absolute configuration of the chiral molecule trans-2,3-dideuterooxirane (C2OD2H2) in the gas phase. The experiment leads to the definitive assignment of the (R,R) configuration to an enantio-selected dideuterooxirane sample with a statistical confidence of 5σ. As the handedness of trans-2,3-dideuterooxirane is unambiguously linked by chemical synthesis to the stereochemical key reference glyceraldehyde, our results provide an independent verification of the absolute configuration of the stereochemical reference standard.